2021
DOI: 10.9734/aprj/2021/v7i430159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Chemical Insecticides and Biopesticides against Flea Beetle in Cabbage (Brassica oleracea var. Capitata)

Abstract: Aims: This study aimed to evaluate chemical insecticides and bio-pesticides against flea beetle in cabbage. Study Design: The experiment was laid out at a randomized complete block design with three replications. Place and Duration of Study: Experimental farm of Sher-e-Bangla Agricultural University, Bangladesh during the period from October 2017 to March 2018. Methodology: The experiment consisted of nine treatments viz. T1(Sevin 85 WP @ 2g/L of water), T2 (Decis 2.5 EC @ 1.0 ml/L of water),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Uma and Manjunatha [42] reported that neem seed kernel extract (5%) proved to be the best among the botanical insecticides against flea beetles on radishes. Neem-based bio-pesticides were effective for the management of flea beetles in different crops [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Uma and Manjunatha [42] reported that neem seed kernel extract (5%) proved to be the best among the botanical insecticides against flea beetles on radishes. Neem-based bio-pesticides were effective for the management of flea beetles in different crops [81,82].…”
Section: Discussionmentioning
confidence: 99%